Influence of feeding practices and season of birth on calf performance - Singh, A.R.; Schalles, R.R.; Smith, W.H.; Kessler, F.B. (Kansas State University. Agricultural Experiment Station, 2011)
The ability of beef cows to produce heavy, vigorous and good quality calves every year is one of their most important economic traits. Feeding practices have been reported to influence average daily gain (ADG) and weaning weight. We evaluated creep-feeding, noncreep-feeding, season of birth, and other factors that affect preweaning performance of calves. At the Fort Hays Branch Experiment Station, Hays, Kansas, purebred sires had been used many generations in the grade Hereford herd. Calves, born in both spring and fall, were randomly allotted to creep-fed and noncreep-fed groups every year. Cows and calves grazed native pastures.
Keywords: Beef; Feed; Birth season; Calf performance; Average daily gain